Rural-Urban Migration in China: Temporary Migrants in Search of Permanent Settlement - Beatriz Carrillo (PORTAL: Journal of Multidisciplinary International Studies, 2004)
Massive population flows from rural to urban areas since the start of economic reform have had consequences on almost every social, economic and political issue in the People's Republic of China. This paper maps the developments of rural to urban migration in reform era China, explaining the repercussions of the household registration system on migration patterns, the economic and social inclusion of rural migrant workers into urban communities, and the formation of migrant communities based on ethnic ties in some of China's major cities. The paper ends with a discussion of the consequences of both regional and rural-urban inequalities on future population flows, and on the possibilities of social tensions brought by the increasing presence of rural migrants in urban China.